2019
DOI: 10.2147/ott.s224521
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Noncoding RNA NEAT1 Promotes Cell Proliferation And Invasion And Suppresses Apoptosis In Hepatocellular Carcinoma By Regulating miRNA-22-3p/akt2 In Vitro And In Vivo</p>

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the most aggressive cancers that is associated with cirrhosis and other chronic liver diseases. Although remarkable progress has been made in past decades, it is still necessary to continue exploring the pathology and development of HCC.ObjectiveIn this study, we elucidated the effect of long noncoding RNA (lncRNA) NEAT1 on HCC development and underlying mechanisms.MethodsClinicopathological features of HCC patients were collected and the correlations with NEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…This group of microRNAs has been extensively studied and has been shown to be downregulated in several cancers, such as gastric cancer, peripheral nerve sheath tumors, esophageal squamous cell carcinoma, melanoma, and breast cancer, among others. 13,34 In these diseases, the increased expression of miR-21 leads to the up-regulation of its downstream targets that are involved in epigenetic modification, metastasis and cell proliferation. 34 miRNA-96 could repress the cancer cell growth and migration respectively in a previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group of microRNAs has been extensively studied and has been shown to be downregulated in several cancers, such as gastric cancer, peripheral nerve sheath tumors, esophageal squamous cell carcinoma, melanoma, and breast cancer, among others. 13,34 In these diseases, the increased expression of miR-21 leads to the up-regulation of its downstream targets that are involved in epigenetic modification, metastasis and cell proliferation. 34 miRNA-96 could repress the cancer cell growth and migration respectively in a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…13,34 In these diseases, the increased expression of miR-21 leads to the up-regulation of its downstream targets that are involved in epigenetic modification, metastasis and cell proliferation. 34 miRNA-96 could repress the cancer cell growth and migration respectively in a previous study. Furthermore, miRNA-96 expression was reduced in endometrioid adenocarcinoma, papillary thyroid carcinoma, ovarian cancer and hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AKT2 is overexpressed in HCC and independently correlated with the prognosis of human HCC 78 . In particular, a study by Zhou et al revealed that NEAT1 positively regulated AKT2 expression by inhibiting miR‐22‐3p, thus, promoting HCC development 79 . Liu et al found that NEAT1 reduced apoptosis and promoted the proliferation of HepG2/Huh7 cells by sponging miR‐let‐7b, thereby emancipating the downstream signalling of insulin‐like growth factor type 1 receptor (IGF‐1R) 80 .…”
Section: Role Of Neat1 In Liver Diseasesmentioning
confidence: 99%
“…Since 2019, there have been four studies reporting its function as a miRNA sponge in the liver by binding to miR-9-5p, miR-21, miR-26b-5p, and miR-214, which target SRY-box transcription factor 11 (SOX11) [50], LDL receptor related protein 6 (LRP6) [51], platelet derived growth factor receptor beta (PDGFRB) [52], and activating transcription factor 4 (ATF4) [53] mRNAs, respectively. Another well-known miRNA sponge, the nuclear paraspeckle assembly transcript 1 (NEAT1) [54] with nine isoforms (ENSG00000245532) with the longest isoform being 22,743 nt (ENST00000501122), binds to let-7a, miR-22-3p, miR-29b, miR-140, miR-146a-5p, miR-155, miR-335, and miR-506 [55][56][57][58][59][60][61][62]. With an lncRNA having many isoforms, the research questions should focus on the identification of isoform-specific function of miRNA sponges, as it is experimentally very challenging to overexpress an isoform with over 10,000 nt in a stable manner.…”
Section: Lncrnas As Microrna Spongesmentioning
confidence: 99%